Surgical treatment of mitral regurgitation: techniques and postoperative results - Filgueira, José L; Abó, Juan C; Rubio, Roberto; Arbiza, Daniel; Baccino, Luis E (Cirugía del Uruguay, 1974)
This report covers a series of 14 patients who underwent substitution of mitral valve. In 11 cases StarrEdward's valve was employed and in the remaining three the valves were made of dura mater. Reasons for surgery, tactics and techniques employed and postoperatory results are described.